Hatchery Waste Meal as Protein Source in Diets for Grower-Finisher Pigs (Sus Domesticus) - Asiedu, Peter (University of Cape Coast, 2020)
The series of experiments reported in this work considered the possibility of utilising hatchery waste as replacement for fish meal in grower finisher diet. An initial survey in the Greater Accra region estimated that as high as 15 (fifteen) tons of waste was generated per annum from just 5 (five) hatcheries. Analysis of the waste showed however, that it had some levels of microbial load, although the presence of Escherichia Coli and Salmonella were not detected. Methods of processing waste using temperature and time combinations showed that simple steaming for 5 minutes at 80°C (5M80T) gave a product that retained high CP as well as had low microbial load suitable for inclusion in feed formulated for pigs. A 16-week study using sixty (60) Large White grower intact male pigs (average liveweight of 17.55 ± 0.1 kg) randomly allotted to 5 dietary treatments [designated 0% Hatchery Waste Meal, 2.5% Hatchery Waste Meal, 5.0% Hatchery Waste Meal, 7.5% Hatchery Waste Meal and 10.0 %] in which HWM replaced Fish Meal directly in the diet. The study again shows that HWM could be processed into a form that can be used after simple processing (steaming) without much loss in nutrient content, particularly protein. The inclusion of HWM up to 5.0% had no significant (p > 0.05) effect on weight gain, feed conversion ratio as well as economy of gain. In the course of the feeding trial, some biochemical and haematological indices assessed also indicated levels within normal ranges for good health in pigs. At the end of the feeding trial the effects of HWM replacement of FM on carcass characteristics (primal cuts, organs weights and measurement of fats) indicated no significant (p > 0.05) dietary treatment effects on all the parameters assessed, except for weight of the empty stomach, GIT (Gastro Intestinal Tract) and thymus gland. Finally, comprehensive survey to determine volumes of HWM generated across hatcheries in Ghana should be done to indicate more accurately the cost saving potential of this feed ingredient for pig fanners in Ghana.
xxi,288p:,ill
Keywords: Animal protein; Average daily gain; Carcass characteristics; Feed intake; Fishmeal; Hatchery waste meal